Fermentation of Allium chinense Bulbs With Lactobacillus plantarum ZDY 2013 Shows Enhanced Biofunctionalities, and Nutritional and Chemical Properties. Issue 10 (26th August 2015) - Pan, Mingfang; Wu, Qinglong; Tao, Xueying; Wan, Cuixiang; Shah, Nagendra P.; Wei, Hua
Abstract: In this study, fermentation of Allium chinense bulbs was carried out with Lactobacillus plantarum ZDY 2013. A decrease in pH from 6.8 to 3.5 and a stable lactic acid bacteria population were observed during 7‐d fermentation. The total phenolic content increased by 2.7‐fold in the aqueous and ethanol extracts of A. chinense bulbs after fermentation. Antioxidant capacity including 2, 2‐diphenyl‐1‐picrylhydrazyl radical‐scavenging effect and reducing power of both extracts was significantly ( P < 0.05) improved after fermentation. Antagonistic test against 6 pathogens showed that fermentation significantly ( P < 0.05) enhanced the antimicrobial activity in both extracts of fermented bulbs, especially in the ethanol extracts of fermented bulbs against L. monocytogenes . Analysis of the free amino acid (FAA) profile by ion‐exchange chromatography revealed that fermentation significantly ( P < 0.05) increased total FAA content. In addition, among 27 kinds of volatile components analyzed by headspace–solid phase microextraction–gas chromatography–tandem mass spectrometry, sulfur‐containing compounds accounted for 65.23%, but decreased to 43.65% after fermentation. Our results suggested that fermentation of A. chinense bulbs with L. plantarum could improve their biofunctionalities, and nutritional and chemical properties.